Does Seasonal Decline in Breeding Performance Differ for an African Raptor across an Urbanization Gradient? - Rose, Sanjo; Sumasgutner, Petra; Koeslag, Ann; Amar, Arjun (Frontiers in Ecology and Evolution, 2017)
As human populations have increased globally, so too has the transformation of natural landscapes into more urban areas. Within Africa, population growth rates and urbanisation rates are amongst the highest in the world, but the impacts of these processes on Africa’s wildlife are largely un-explored. In this study, we focus on a recently established population of black sparrowhawks Accipiter melanoleucus in Cape Town, South Africa. Using long-term data (16 years), we investigate the relationship between the timing of breeding and breeding performance along an urban gradient. We found no evidence for a direct effect of urbanisation on either timing of breeding or breeding performance. However we did find some evidence for a differential seasonal decline in breeding performance dependent on the levels of urbanisation. Thus, higher productivity was found in more urbanised habitats earlier in the season, but toward the end of the breeding season, birds in less urbanised habitats performed better. Our study represents one of the first to examine avian productivity in relation to urbanisation in Africa, and also represents one of the first studies to suggest that seasonal declines in productivity may differ according to levels of urbanisation. These results have considerable implications for potential changes in phenology or productivity for the regions’ avifauna as African urbanisation continues.